On the general Erd\H{o}s-Moser equation via the notion of olloids - Agama, Theophilus (My University, 2022)
We introduce and develop the notion of the olloid. We apply this notion to study a variant and a generalized version of the Erd ̋os-Moser equation under some special local condition.
Keywords: olloid